Nutritional and Functional Potential of Developed Low-Cost Leaf-Based Spreads: A Sustainable Approach for Enhancing Nutrition and Health - Pal, A. D.; Ismail, F.; Banerjee, A. (Journal of Scientific Research, 2026)
Green edible leaves are a sustainable and economical solution for promoting health and nutrition. Nonetheless, their consumption remains limited due to insufficient awareness and appealing recipes. This study explores the nutritional and functional properties of leaf-based spreads made from lesser-known edible leaves (Capsicum frutescens and Typhonium trilobatum), highlighting their potential as low-cost solutions for alleviating hidden hunger. Spreads containing C. frutescens (CS), T. trilobatum (TS) and both the leaves (CTS) prepared in 3 variations each were analyzed for their sensory attributes. Variation 3 of each spread (CS3, TS3, and CTS3) demonstrated highest sensory score along with moderate macronutrients and a significant presence of micronutrients, fibre and functional properties compared to the control. Notably, higher amounts of iron, calcium, magnesium, phosphorous, vitamin C (11.28, 110.11, 68.78, 79.01, 56.30 mg/100 g), β carotene (495.03 µg/100 g), phytochemicals namely, flavonoids, alkaloids, and total phenols (66.34, 93.43, and 346.15 µg/100g), as well as antioxidant, antibacterial, and prebiotic potential were noted in CS3 than TS3 versus control. Interestingly, the spreads prepared by combining both leaves (CTS3) showed the highest nutritional and functional profile, indicating a synergistic combination. Hence, consumption of these spreads, especially CST3 followed by CS3 and TS3, may mitigate nutritional insecurity and advance health.